Evaluation of the psychometric properties of the portuguese peabody developmental motor scales - 2 edition: a study with children aged 12 to 48 months - Rebelo, M. (2021)
The purpose of this study was to examine the psychometric properties of Peabody Developmental Motor Scales II (PDMS-2-Folio and Fewell, 2000) using a Portuguese sample. The validation of the Portuguese version of the PDMS-2 was applied according to the manual, for 392 children, from two institutions, from 12 to 48 months, with an analysis of the internal consistency (α Cronbach), of test–retest reliability (ICC) and construct validity (confirmatory factor analysis). The results of the confirmatory factorial analysis (χ2 = 55.614; df = 4; p = 0.06; χ2/df =13.904; SRMR (Standardized Root Mean Square Residual) = 0.065; CFI (Comparative Fit Index) = 0.99, TLI = 0.99, RMSEA (Root Mean Square Error of Approximation) = 0.068) of two factors (Gross Motor and Fine Motor) as the original version but correlated. Most of the subtests had good internal consistency (α = 0.85) and good test–retest stability (ICC = 0.98 to 0.99). The results indicated that the Portuguese version of the PDMS-2 is adequate and valid for assessing global and fine motor skills in children aged 12 to 48 months, and can be used as a reference tool by health and education professionals to assess motor skills and, thus, allowing to detect maladjustments, deficiencies or precocity, so that children can later receive appropriate intervention.